FIXING JEJUNAL MANEUVER TO PREVENT PETERSEN HERNIA IN GASTRIC BYPASS - MURAD-JUNIOR,Abdon José (2015)
Background : Among Roux-en-Y gastric bypass complications is the occurrence of intestinal obstruction by the appearance of internal hernias, which may occur in Petersen space or the opening in mesenteric enteroenteroanastomosis. Aim : To evaluate the efficiency and safety in performing a fixing jejunal maneuver in the transverse mesocolon to prevent internal hernia formation in Petersen space. Method : Two surgical points between the jejunum and the transverse mesocolon, being 5 cm and 10 cm from duodenojejunal angle are made. In all patients was left Petersen space open and closing the opening of the mesenteric enteroenteroanastomosis. Results : Among 52 operated patients, 35 were women (67.3%). The age ranged 18-63 years, mean 39.2 years. BMI ranged from 35 to 56 kg/m2 (mean 40.5 kg/m2). Mean follow-up was 15.1 months (12-18 months). The operative time ranged from 68-138 min. There were no intraoperative complications, and there were no major postoperative complications and no reoperations. The hospital stay ranged from 2-3 days. During the follow-up, no one patient developed suspect clinical presentation of internal hernia. Follow-up in nine patients (17.3%) showed asymptomatic cholelithiasis and underwent elective laparoscopic cholecystectomy. During these procedures were verified the Petersen space and jejunal fixation. In all nine, there was no herniation of the jejunum to the right side in Petersen space. Conclusion : The fixation of the first part of the jejunum to left side of the transverse mesocolon is safe and effective to prevent internal Petersen hernia in RYGB postoperatively in the short and medium term. It may be interesting alternative to closing the Petersen space.